Calculation of the Stability of the Fiber Ring Laser with Liquid Crystal Polarization Controllers - Hnatenko, O. S.; Obozna, V. P. (Sumy State University, 2018)
To date, with the ultra-short pulse lasers are used in many areas of science and technology, including information technology. The main task of creating such lasers is to provide output radiation with the shortest pulse duration. The shortest duration pulses achieved in fiber ring lasers with nonlinear rotating polarization modes, namely 20 fs. But in such lasers, there are a number of problems: stability of operation and tuning of the mode locking. This is due to the tuning of the mode-locked by rotating the wave plates in space manually.
Keywords: information technology; інформаційні технології; информационные технологии; radiation; излучение; polarization modes; режими поляризації; поляризационные режимы